Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja Pegawai dengan Kepuasan Kerja sebagai Variabel Mediasi di UPT Puskesmas Tanjung Rejo Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Anastasya, Kristina Realita; Chaniago, Sabaruddin; Rizki, Ainur (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of compensation and work environment on employee performance with job satisfaction as a mediating variable at the UPT Puskesmas Tanjung Rejo, Percut Sei Tuan District, Deli Serdang Regency. This research is motivated by the importance of employee performance in improving the quality of health services, as well as indications of mismatches in compensation and working conditions that affect employee satisfaction and performance. This study uses a quantitative approach with a survey method. The research sample consisted of 44 respondents determined using the Slovin formula from a population of 78 employees. Data collection was carried out through the distribution of questionnaires, which were then analyzed using multiple linear regression analysis with the help of SPSS version 27. Data testing was conducted through classical assumption tests, t-tests, coefficient of determination tests (R²), and the Sobel test to determine the role of the mediating variable. The results of the study show that compensation and the work environment have a positive and significant effect on employee performance. In addition, compensation and the work environment also have a positive and significant effect on job satisfaction. Job satisfaction is proven to have a positive and significant effect on employee performance and acts as a mediating variable that strengthens the influence of compensation and the work environment on employee performance. This study concludes that providing fair compensation and a conducive work environment can increase job satisfaction, which in turn leads to improved employee performance. The results of this study are expected to serve as a consideration for management in improving the quality of human resources and health services.